Growing futures: Youth empowerment through home gardening initiatives in Fiji - Deesh, Aradhana Devi; Bai, Seremaia (Ministry of Agriculture, Fiji, 2023)
The COVID-19 pandemic has had profound effects on various aspects of society, including food and nutrition security. One solution that had gained momentum in Fiji was home gardening, which empowered individuals and families to cultivate their own food and enhance their nutritional intake. The aim of this study was to understand how youth empowerment played a vital role in promoting sustainable and resilient practices, particularly for those who were in the early career of professional rugby, which is the national sport of Fiji. This study highlights the significance of gardening initiatives in Fiji as a pathway to youth empowerment and sustainable development. A total of 20 youths were identified and supplied with seeds/seedlings, crop starter guides, planting techniques, pest management strategies, and agro-inputs as part of the Home Gardening Program initiated by the Fiji Ministry of Agriculture in 2020. Through the ARSF II project, a survey on the impact of home gardening and youth involvement was studied. The finding of the study revealed that the youths gained valuable skills in home gardening including plant/soil health, produced fresh vegetables to meet the nutritional needs of the family, generated income from the sale of the extra produce, and acquired farming skills. It further explored the innovative concept of AgroRugby as a powerful tool for empowering youth in Fiji. By combining the values and skills cultivated in rugby with the transformative potential of gardening, this study investigated the unique opportunities for empowerment and personal growth that arise from this synergistic approach.